Familial Mediterranean fever: perspective on female fertility and disease course in pregnancy from a multicenter nationwide network - DURUÖZ, MEHMET TUNCAY (My University, 2023)
The aim of this study was to analyze the pregnancy process, especially the Familial Mediterranean fever (FMF) disease course and attack types during pregnancy, and to examine the relationship between disease-related factors and female infertility in FMF patients. The study, which was planned in a multicenter national network, included 643 female patients. 435 female patients who had regular sexual intercourse were questioned in terms of infertility. Pregnancy and delivery history, FMF disease severity and course during pregnancy were evaluated. The relationship between demographic and clinical findings, disease severity, genetic analysis results and infertility was investigated. 401 patients had at least 1 pregnancy and 34 patients were diagnosed with infertility. 154 patients had an attack during pregnancy. 61.6% of them reported that attacks during pregnancy were similar to those when they were not pregnant. The most common attack symptoms were fever, fatigue and abdominal pain-peritonitis (96%, 87%, and 83%, respectively) in the pregnancy period. The disease-onset age, disease activity score, gene mutation analyses, and regular colchicine use (> 90%) were similar between the fertile and infertile groups, while the frequency of previous appendectomy and alcohol consumption rates were higher in individuals with infertility. Our results indicated no significant change in the frequency and severity of attacks during pregnancy. The low rate of infertility (7.8%) in our patients was noted. It has been suggested that the risk of FMF-related infertility may not be as high as thought in patients who are followed up regularly and received colchicine.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology; Amyloidosis; Colchicine; Infertility; Pregnancy; Serositis